Post-traumatic stress disorder following implantable cardioverter defibrillator shocks: a hidden cost of life-saving therapy - Desai, Twaraa M.; Shukla, Pranav S.; Shah, Himal R.; Sharma, Nishant P. (International Journal of Research in Medical Sciences, 2025)
Although implantable cardioverter-defibrillators (ICDs) play a critical role in preventing sudden cardiac death, the very shocks that preserve life can paradoxically become a source of long-term psychological harm. PTSD following ICD shocks remains an underrecognized diagnosis, despite mounting evidence linking it to declines in mental health, quality of life, and even cardiovascular prognosis itself. Patients may experience intrusive re-experiencing of trauma, persistent hypervigilance, avoidance behaviors, and anticipatory anxiety: symptoms that not only disrupt daily functioning but can also interfere with treatment adherence and long-term treatment outcomes. A review was conducted of literature published between January 2008 and May 2024 using PubMed, Scopus, and Web of Science databases. Emphasis was placed on patient-reported outcomes, intervention efficacy, and gaps in clinical practice. ICD shocks, particularly when inappropriate or clustered, have been linked to clinically significant PTSD symptoms in as many as 38% of recipients. Proposed mechanisms span heightened sympathetic arousal, maladaptive fear conditioning, and neurobiological changes involving key limbic structures. Risk appears to be elevated among younger patients, women, individuals with preexisting trauma histories, and those with comorbid anxiety or depressive disorders. Validated tools like the PCL-5 and Florida shock anxiety scale (FSAS) offer practical means of detecting distress, and growing evidence supports the benefit of interventions such as trauma-focused cognitive-behavioral therapy, SSRIs, EMDR, and tailored device programming. Routine screening, shock-minimization strategies, and integration of psychological services into device clinics are essential. Future studies should address long-term outcomes, standardized interventions, and guideline development for multidisciplinary management.